(untitled) (Bangladesh Journal of Child Health, 2017)
Hand, foot, and mouth disease (HFMD) also known as vesicular stomatitis with exanthema, first reported in New Zealand in 1957 is caused by Coxsackie virus A16 (CVA16), human enterovirus 71 (HEV71) and occasionally by other HEV-A serotypes, such as Coxsackie virus A6 and Coxsackie virus A10, are also associated with HFMD and herpangina. While all these viruses can cause mild disease in children, EV71 has been associated with neurological disease and mortality in large outbreaks in the Asia Pacific region over the last decade. It is highly contagious and is spread through direct contact with the mucus, saliva, or feces of an infected person. This is characterized by erythrematous papulo vesicular eruptions over hand, feet, perioral area, knee, buttocks and also intra-orally mostly in children, typically occurs in small epidemics usually during the summer and autumn months. HFMD symptoms are usually mild and resolve on their own in 7 to 10 days. Treatment is symptomatic but good hygiene during and after infection is very important in preventing the spread of the disease. Though only small scale outbreaks have been reported from United States, Europe, Australia Japan and Brazil for the first few decade, since 1997 the disease has conspicuously changed its behavior as noted in different Southeast Asian countries. There was sharp rise in incidence, severity, complications and even fatal outcomes that were almost unseen before that period. There are reports of disease activity in different corners of India since 2004, and the largest outbreak of HFMD occurred in eastern part of India in and around Kolkata in 2007and Bhubaneswar, Odisha in 2009. In recent years there are cases of HFMD have been seen in Bangladesh also. Although of milder degree, continuous progress to affect larger parts of the neighboring may indicate vulnerability of Bangladesh from possible future outbreaks. Bangladesh J Child Health 2016; VOL 40 (2) :115-119